Developing Digital Microlearning Content on Reaction Rates Using Wix for Senior High School - Fajriah, Sari Nur; Paristiowati, Maria; Nanda, Elsa Vera (Journal of Educational Management and Learning, 2025)
Reaction rate concepts in high school often lack submicroscopic depth and are not supported by digital media that match Generation Z's preferences for interactive learning. This study developed a Wix-based microlearning platform for 11th-grade students featuring videos, infographics, quizzes, worksheets, games, and modules. Using the ADDIE model, the platform was evaluated by experts and tested in the classroom. Expert validation showed high feasibility (91.94% from content and language experts, 90.40% from media experts). Large-scale trials with students and teachers also yielded high acceptance (93.25% and 93.23%, respectively). These findings support the platform’s feasibility and effectiveness in enhancing chemistry learning, especially for teaching reaction rates.